Relational Equality and Disability Injustice - Brown, Jeffrey M. (Journal of moral philosophy, 2019)
Disabled people suffer from pervasive inequalities in employment, education, transportation, housing, and health care compared to those who are not disabled. Moreover, people with disabilities are often subject to unjustified stigma and pity. In this paper, I will explain why these disadvantages violate relational egalitarian principles of justice. As I will show, my argument can account for both kinds of inequality that disabled people face.